Open-cell polyurethane foams of very low density modified with various palm oil-based bio-polyols in accordance with cleaner production. (25th March 2021) - Polaczek, Krzysztof; Kurańska, Maria; Auguścik-Królikowska, Monika; Prociak, Aleksander; Ryszkowska, Joanna
Abstract: Commercially available polyurethane foams are produced mainly from raw materials of petrochemical origin. Vegetable oils have the potential to be inexpensive and widely available resources for the synthesis of polyol compounds. The research presented here describes use of renewable and waste materials for synthesis of open-cell polyurethane foams. This paper discusses the results of studies on the influence of the palm oil's origin on the properties of bio-polyols. Three oil versions have been chosen: refined, unrefined, as well as used cooking palm oil. A two-stage method based on epoxidation and oxirane ring opening was used to synthesize bio-polyols and these were characterized by hydroxyl values from 150 to 156 mgKOH/g. The open-cell polyurethane foam was synthesized and modified by replacing 20 wt% of petrochemical polyol with bio-polyols synthesized from palm oil. It was found that the modified polyurethane foams comply with requirements for commercial products. The modified foams were characterized by thermal conductivity ranging from 39 to 42 mW/m·K, and apparent densities between ca. 13 and 15 kg/m 3 . What is more, addition of bio-polyol from unrefined oil and used cooking oil had a beneficial effect on the mechanical strength of the resulting foams. The foams were characterized by more than 95% open-cell content. Highlights: Used cooking palm oil is an inexpensive and easily accessible raw material. Palm oils of various origins were functionalized into reactive polyols. Palm oil-based polyols were used to prepare low density open-cell PUR foams. The origin of palm oil-based polyol has an influence on PUR foam properties.